Deep Cross-Corpus Speech Emotion Recognition: Recent Advances and Perspectives - Zhang, Shiqing; Liu, Ruixin; Tao, Xin; Zhao, Xiaoming (Frontiers in Neurorobotics, 2021)
Automatic speech emotion recognition (SER) is a challenging component of human-computer inter-action (HCI). Existing literatures mainly focus on evaluating the SER performance by means of training and testing on a single corpus with a single language setting. However, in many practical applications, there are great differences between the training corpus and testing corpus. Due to the diversity of different speech emotional corpus or languages, most previous SER methods do not per-form well when applied in real-world cross-corpus or cross-language scenarios. Inspired by the pow-erful feature learning ability of recently-emerged deep learning techniques, various advanced deep learning models have increasingly been adopted for cross-corpus SER. This paper aims to provide an up-to-date and comprehensive survey of cross-corpus SER, especially for various deep learning techniques associated with supervised, unsupervised and semi-supervised learning in this area. In addition, this paper also highlights different challenges and opportunities on cross-corpus SER tasks, and points out its future trends.